Weeds distribution and abundance in irrigated fields of White Nile State - Elkhawad, Mohamed; Abdalla, Amna; Osman, Abosofian (International Journal of Environment, 2015)
Field survey was conducted during the summer season of 2011- 2012 to determine the weed flora and weed dominance at the irrigated sites of White Nile State. The State was divided into six irrigated sites from which a total of thirty- five fields were selected and ten quadrates (1m2) from each field were taken randomly. In each quadrate individual weed species were recorded. Field frequency, uniformity and mean field density were also determined for each weed. Fifty five weed species belonging to twenty- four families (three monocotyledonous and twenty- one dicotyledonous) were recorded. Brachiaria eruciformis, Brachiaria reptans, Thunbergia annua and Ipomoea cordofana were the most dominant weed species in most fields. The highest Abundance Index were recorded by Ipomoea cordofana at El Salam and El Dawium counties (208.16 and 116.35), Brachiaria eruciformis at Um Remta and El Gebalen counties (158.80 and 79.23), Brachiaria reptans at Kosti (116.54) and Momordica balsamina at Gezira Aba county (90.06). Brachiaria eruciformis showed the highest MFD and Uniformity at El Salam and Um Remta Counties (19.11 and 80.00), respectively, and highest frequency value was recorded by Ipomoea cordofana (142.86) at El Salam County. The AI which used as weed survey method is to evaluate the weed management strategies and the change of weed species in weed communities through years. International Journal of Environment Vol.4(4) 2015: 45-61